Pelaporan Biaya Lingkungan Sebagai Alat Bantu Bagi Pengambilan Keputusan Yang Berkaitan Dengan Pengelolaan Lingkungan - Agustia, Dian (AKRUAL: JURNAL AKUNTANSI, 2010)
AbstractEnvironmental accounting is a term associated with the inclusion of environmental costs into corporate accounting practices.The proportion ofenvironmental costsis20% oftotalÂ  operational costs company. Environmental costsare groupedinenvironmentalmedia, amongothers: (a) water/climate, (b) Wastewater, (c) waste, (d) soil/groundwater, (e) noise/vibration, (f) biodiversity/landscape, (g )radiation. Classification ofenvironmental mediais based onUnitedNationsStatisticsDivisionpublicationentitledIntegratedEnvironmentaland EconomicAccounting. The mediaenvironmentisrepresentedcategoriesof environmentalimpactscausedtonature.